THE ROLE OF WHILE-LISTENING ACTIVITIES IN EFL TEACHING - Umaraliyeva Munojat Mashrabovna; Gulnoza Qahorova Abduqobil qizi (Лучшие интеллектуальные исследования, 2024)
This article covers many fun activities to improve listening comprehension skills, provides information and techniques that are very useful for students learning a second foreign language, and explains the types of listening comprehension and its importance